Acute effects of Δ9-tetrahydrocannabinol on computational measures of neurocognitive processes are related to recent cannabis use among adolescents and young adults - Paige, K. J.; Weigard, A. S.; Ajilore, O.; Phan, K. Luan; de Wit, H.; Klumpp, H.; Crane, N. A. (Frontiers in Adolescent Medicine, 2025)
IntroductionCannabis and its main psychoactive constituent, delta-9-tetrahydrocannabinol (THC), are thought to weaken neurocognitive processes. However, past experimental research examining the acute effects of THC on neurocognition has produced mixed results. The current study aims to advance this literature through application of computational modeling and consideration of individual differences in cannabis use history and subjective drug effects.MethodsIn a double-blind THC administration experiment, N = 30 healthy late adolescent and young adult occasional to regular cannabis users (53% men; ages 18–25) received THC (7.5 mg, oral) and placebo. They completed a Go/No Go (GNG) task at the time of peak drug effect. We analyzed GNG data using the drift diffusion model, which provides measures of effects of THC on three components of neurocognition: cognitive efficiency (drift rate), response caution (boundary separation), and motor response execution processes (non-decision time). Bayesian statistical methods were used to assess relations between individuals’ neurocognitive parameter differences across the experimental conditions (THC—placebo) and several relevant covariates (cannabis use history and subjective drug effects).ResultsOverall, THC vs. placebo did not significantly alter any parameter. However, THC was associated with greater between-person variability in both drift rate and nondecision time, suggesting heterogeneity in the effects of the drug. THC weakened cognitive efficiency (slower drift rates) to a greater extent in participants with less cannabis use. Further, stronger subjective effects (drug “effect” and drug “high”) were related to poorer cognitive efficiency during THC intoxication.DiscussionResults add to our understanding of the acute neurocognitive effects of THC. Slower cognitive efficiency after THC was highly heterogeneous, and was related to both recent cannabis use and subjective drug effects. These findings support the notion that acute effects of cannabis on cognitive efficiency (GNG drift rate) are reduced by individuals’ tolerance to cannabis.